Transfusion of stored autologous blood in patients with low-grade pseudomyxoma peritonei: A retrospective analysis of its safety and outcome - Gao, Xiaoyun; Kou, Liduo; Guan, Hang; Tian, Hua; Jia, Junhui; Bai, Yu; Bai, Wei; Di, Yanhui; Ma, Ruiqing; Wang, Xinhua (Frontiers in Oncology, 2022)
Background Pseudomyxoma peritonei is a rare disease that presents as a malignant tumor on the peritoneal surface. Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy is the standard treatment for this disease and frequently requires a red blood cell transfusion. However, due to the limited collection and supply of allogeneic blood, surgical treatment may be delayed due to inadequate preparation of allogeneic blood in the course of clinical treatment. This study aimed to evaluate the safety and efficacy of transfusion of stored autologous blood in patients with low-grade pseudomyxoma peritonei. Methods Pseudomyxoma peritonei patients who received cytoreductive surgery combined with heat-infused peritoneal chemotherapy were divided into two groups: transfusion of allogeneic blood and transfusion of stored autologous blood. A comparison of the differences in multiple factors between the two groups was performed, including tumor recurrence, survival time, hemoglobin and hematocrit levels, coagulation function (prothrombin time, activated partial thromboplastin time, and fibrinogen), total hospital stay duration, and incidence of serious adverse events after surgery. Results Propensity score matching analysis yielded 34 patients with allogeneic blood transfusion and 34 patients with stored autologous blood transfusion. Comparison analysis did not show statistical differences in several factors, including age, tumor grade, tumor recurrence rate after surgery, etc., between the two groups. The cytoreductive degree was considered an independent risk factor for tumor recurrence. The pseudomyxoma peritonei patients in the autologous transfusion group had a higher 5-year survival rate and a longer survival time. Moreover, transfusion of stored autologous blood did not increase the rate of tumor recurrence, or the total hospital stay duration after surgery, the hemoglobin level and coagulation function were well stabilized within 24 h after surgery, and there was a low incidence of serious adverse events. Conclusion The clinical application of transfusion of stored autologous blood in pseudomyxoma peritonei patients is safe and effective.